1980
DOI: 10.1039/c39800000839
|View full text |Cite
|
Sign up to set email alerts
|

Electrocrystallised metal–tetracyanoquinodimethane salts with high electrical conductivity

Abstract: Conductivities/Q-l cm-l from ca.to 800 [for Cu(TCNQ)] are obtained for salts, often novel, of the formulation M(TCNQ), or M(TCNQ), (solvent),, prepared by cathodic electrocrystallisation from tetracyanoquinodimethane (TCNQ) in the presence of metal (M) salts, where the M are

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 0 publications
0
34
0
1
Order By: Relevance
“…The nanoscale electrocrystallization can potentially be applied to various organic conductors because it is based on the bulk electrocrystallization. 10 In particular, Kathirgamanathan et al [20][21][22] have reported that the bulk electrocrystallization of this material with tetra--n--butylammonium nitrate in acetonitrile yields bulk single crystals that consist of partially oxidized TTF molecules. Tetrathiafulvalene (TTF, Figure 1) is well known as a component of organic conducting crystals.…”
Section: -15mentioning
confidence: 99%
“…The nanoscale electrocrystallization can potentially be applied to various organic conductors because it is based on the bulk electrocrystallization. 10 In particular, Kathirgamanathan et al [20][21][22] have reported that the bulk electrocrystallization of this material with tetra--n--butylammonium nitrate in acetonitrile yields bulk single crystals that consist of partially oxidized TTF molecules. Tetrathiafulvalene (TTF, Figure 1) is well known as a component of organic conducting crystals.…”
Section: -15mentioning
confidence: 99%
“…Both ions, continuously produced during the electrolysis reaction, migrate in the electric field to the opposite electrodes and precipitate as CuTCNQ in the presence of their counterions. Whereas the cathode reaction has already been used to form CuTCNQ films on vitreous carbon, gold, and platinum from ACN solution containing TCNQ and Cu + or Cu 2+ , 18,19 and TCNQ crystals in H 2 O containing Cu 2+ , 20,21 no paper has reported on electrodeposition of CuTCNQ on Cu substrates by the anode reaction. The most likely reason for this might be the impossibility to control the process electrochemically since Cu metal in a TCNQ containing ACN solution reacts already spontaneously without applied voltage ͓Eq.…”
Section: ͑1͒mentioning
confidence: 99%
“…Comparison of the different metal ions reveals that the M-N distances in the alkali-metal salts and in the thallium Slow diffusion of solutions of DCNQIs and metal iodides [66] or electrocrystallization [67] were utilized in growing crystals of the salts under discussion. Moreover, single crystals of DCNQI copper or silver salts can easily be grown by immersion of a copper or silver wire, respectively, in a solution of DCNQIs in acetonitrile.r68.…”
Section: Structural Propertiesmentioning
confidence: 99%